2018
DOI: 10.3389/fpsyt.2018.00498
|View full text |Cite
|
Sign up to set email alerts
|

“Opening a Door to a New Life”: The Role of Forgiveness in Healing From Moral Injury

Abstract: For military veterans struggling with moral injury, forgiveness can become both an animating concern and a potential path to healing. In this perspective piece, we draw on our clinical work and research findings to examine why forgiveness matters to veterans who feel guilt and shame about their actions in war, what type of forgiveness is attainable and meaningful, and what role clinicians can play in facilitating forgiveness. We conclude by reflecting on the potential, as well as the limits and tensions, of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…A recent meta-analysis of the neural correlates of guilt identified multiple areas, primarily in the left hemisphere (red circles) (6). (9)(10)(11). Two studies of healthy individuals have identified neural correlates related to forgiving others for transgressions (12,13).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A recent meta-analysis of the neural correlates of guilt identified multiple areas, primarily in the left hemisphere (red circles) (6). (9)(10)(11). Two studies of healthy individuals have identified neural correlates related to forgiving others for transgressions (12,13).…”
mentioning
confidence: 99%
“…Several treatment approaches designed specifically to promote healing from moral injury have been developed, and preliminary studies suggest value (11,65). One challenge is recognition that in some cases the patient's beliefs and judgements about their experiences are factually correct (9,10,66). Thus, acknowledgment of the past moral/ethical violations (i.e., opening up) may be essential to begin the healing process (9)(10)(11).…”
mentioning
confidence: 99%
See 3 more Smart Citations